Application of Pharmacology Knowledge of General Practice Nursing Students during Clinical Nursing Practices - Klevinskytė, Martyna; Galdikienė, Nijolė (Slauga. Mokslas ir praktika, 2025)
Medication errors cause thousands of deaths worldwide every year. Students graduating from the general practice nursing programs will be responsible for the medication administration process, which influences the quality of treatment and care process and the patients’ health. It is of importance for the academic community training nurses to constantly monitor and evaluate the general and clinical pharmacology knowledge of future nurses, strive to present the knowledge as clearly as possible during lectures, practical sessions, and clinical nursing practices, and analyze the most commonly occurring errors, along with their causes, in order to implement the latest teaching methods, and run programs to help avoid any errors. The aim of the study is to determine the application of pharmacology knowledge by general practice nursing students during clinical nursing practices. Research methods: A quantitative study was conducted using the questionnaire survey method developed by the author to collect subject-related data. 120 students of the nursing program were surveyed. Results. The knowledge of second to fourth-year students in the general practice nursing program about nursing actions in the medication administration process is deemed to be sufficient. It has been found that students are well-versed in all stages of the medication administration process. The results of the study suggest that the knowledge and practical skills of the future general practice nurses will allow for quality, professional, and safe nursing care in the future, thereby ensuring better treatment and care process outcomes.
Keywords: nursing students; pharmacological knowledge; clinical nursing practices